Oxidative stress and hormesis in evolutionary ecology and physiology A Marriage between mechanistic and evolutionary approaches - COSTANTINI, DAVID (Sringer, 2014)
This book discusses oxidative stress and hormesis from the perspective of an evolutionary ecologist or physiologist. In the first of ten chapters, general historical information, definitions, and background of research on oxidative stress physiology, hormesis, and life history are provided. Chapters 2-10 highlight the different solutions that organisms have evolved to cope with the oxidative threats posed by their environments and lifestyles. The author illustrates how oxidative stress and hormesis have shaped diversity in organism life-histories, behavioral profiles, morphological phenotypes, and aging mechanisms. The book offers fascinating insights into how organisms work and how they evolve to sustain their physiological functions under a vast array of environmental conditions.